Islam in the Nordic and Baltic Countries (Islamic Studies Series) - Fatemeh Shayan (International Institute of Islamic Thought, 2011)
Until recently, scholarly writing on Islam in the Nordic and Baltic regions has proved to be a woefully scant enterprise. Most works that have emerged on the topic of Islam in Europe focus on the United Kingdom and France, leaving northern and eastern European regions largely underanalyzed. It is in this respect that Göran Larssonʼs edited volume is to be welcomed as an important and long overdue contribution to the topic ...